DAMPAK PEMBANGUNAN PLTU ROPA TERHADAP PEMBANGUNAN BERKELANJUTAN DI DESA KELIWUMBU KECAMATAN MAUROLE KABUPATEN ENDE - Andris, Adrianus Mbele Nuwa; Ballo, Fransina W.; Tiwu, Maria Indriyani Hawe (Elastisitas : Jurnal Ekonomi Pembangunan, 2024)
This research aims to explain the impact of the construction of the Ropa PLTU on sustainable development in Keliwumbu Village, Maurole District, Ende Regency, in the form of socio-economic and environmental impacts on the community of Keliwumbu Village. This research uses a qualitative descriptive approach with data collection techniques used are interviews, observation and documentation. The research results show that the development of the Ropa PLTU industry has had an impact on sustainable development in the socio-economic dimension of the Keliwumbu Village community in the form of changes in community income, availability of employment opportunities, opening up of new economic business opportunities, changes or additions to sources of livelihood, good community education and quality of health. society is not good. The environmental impact is environmental pollution felt by the people of Keliwumbu Village, pollution caused by PLTU liquid waste and coal loading and unloading dust which pollutes the ocean and beach sand turns black, and coal loading and unloading dust causes air pollution, reducing fishermen's catches and harvests. farmers, highways are damaged due to passing coal-laden vehicles.